Letter (copy) : Danger of political persecution in Spain - Citrine, Walter, 1887-1983
024_0009_001 Secretary's. WMC/HVT/FC/32 Mr. A. Fenner Brockway, The Independent Labour Party, 35, St. Bride Street, E.C.4. 8th October, 1938. Dear Mr. Brockway, DANGER OF POLITICAL PERSECUTION IN SPAIN With further reference to your lettor of the 3rd instant I may say that after consultation with members of the National Council of Labour a communication has been sent to the Spanish Ambassador in London pointing out our concern in regard to reports received in connection with the trial on October 11th,and asking for an appointment with him on Monday in order that the question may be fully dealt with. I may say that an endeavour was made to make contact with the Ambassador yesterday and this morning, but he is not available. I understand that you are aware, through Mr. Gillies, of the activities of Adler and de Brouckere. Yours sincerely, General Secretary. 292/946/24/9